Implikasi Dan Faktor yang Mempengaruhi Keterlambatan PPAT dalam Mendaftarkan APHT Ke Kantor Pertanahan - Simanungkalit, Rosalina; Farma Rahayu, Mella Ismelina (UNES Law Review, 2024)
Implications and Factors Affecting PPAT Delay in Registering APHT to the Land Office, with the object of research is APHT to be registered APHT, this article aims to find out the Implications and Factors Affecting PPAT Delay in Registering APHT to the Land Office, with normative methods. The result is that the Land Deed Official (PPAT) in making the Deed of Granting Mortgage Rights (APHT) starts from the process of checking juridical data and documents, here the PPAT must be careful in checking the documents and is responsible for the implications caused by the PPAT's inaccuracy in checking, The second is in the process of APHT registration to the Land Office where the PPAT must be responsible for being on time according to Article l3 Paragraph (2) which states that no later than 7 working days after signing the APHT, the PPAT must send the APHT and other necessary documents to the Land Office. The 7-day grace period is calculated from the time the APHT is signed. Factors influencing the delay in the implementation of APHT making are first, from the parties who take a long time in collecting documents or exceeding the time limit, second, checking the Land Rights certificate at the Land Office which is said to be too long, third, namely writing errors in the deed, fourth, namely delays in APHT registration